MASSIMILIANO BAMPI, CAROLYNE LARRINGTON, AND SIF RIKHARDSDOTTIR (eds.): A Critical Companion to Old Norse Literary Genre. Studies in Old Norse Literature 5, D.S. Brewer, Cambridge 2020. Pp. xiv + 374; 6 figures, 1 chart. ISBN 978-1-84384-564-5. Issue 1 (2020) - McTURK, RORY
No abstract available